IMPROVEMENT OF LEUKEMIC RETINOPATHY AFTER LEUKAPHERESIS IN CHRONIC MYELOGENOUS LEUKEMIA WITH LEUKOSTASIS - Ruchyta Ranti; Sauli Ari Widjaja; Wimbo Sasono; Muhammad Firmansjah; Ima Yustiarini; Ady Dwi Prakosa; Moestidjab Moestidjab; Gatut Suhendro (International Journal of Retina, 2020)
ABSTRACT Introduction: to report a case of bilateral leukemic retinopathy due to leukostasis that was successfully managed by leukapheresis. Case Presentation: 31-year-old male with mild visual disturbance was referred to ophthalmology department. He suffered from Chronic Myelogenous Leukemia (CML) with white blood cell (WBC) count 533.900/microL. He was started on hydroxyurea, allopurinol, and once leukapheresis. Ophthalmologic evaluation revealed visual acuity of 4/4 in the right eye and 4/6,3 in the left eye. Funduscopy examination showed the presence of bilateral papilledema, venous engorgement, tortuosity, and retinal hemorrhages. Then this patient continued with second leukapheresis. Result: Visual acuity, laboratory examination, and funduscopic finding was evaluated. His visual acuity was improved, papilledema and retinal blood vessels abnormality had markedly reduced concurring with the patient’s hematological remission. Decreasing WBC count after leukapheresis has improved blood flow that reflected from the retinal findings and visual acuity improvement. Conclusion: Leukapheresis treatment is sufficient to improved clinical condition for leukemic retinopathy caused by CML with leukostasis. Keywords: chronic myelogenous leukemia (CML), hyperleukocytosis, leukostasis, leukemic retinopathy